Time to Restructure the Ukrainian National Association: Here's Why and How - Olesnycky, Damian (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: The Ukrainian National Association (UNA) is a Ukrainian-American fraternal benefit society based in Parsippany, New Jersey. Founded in 1894 to help poor Ukrainian immigrants pay for funerals and support ailing family members, its mission is to preserve Ukrainian culture in North America and to provide its members with financial products and services, primarily in the form of life and disability insurance. During its first century of existence, the organization amassed a sizable membership base and a considerable amount of wealth by catering to three large waves of Ukrainian immigrants. The UNA harnessed its resources adeptly, founding numerous cultural institutions (referenced in this report as fraternal activities ) and becoming a powerful advocate for Ukrainians worldwide. As a result, the association played a central role in the formation of the Ukrainian-American and Ukrainian-Canadian identities. The past decade, however, has been a difficult stretch for the UNA. The insurance business, the association s longtime economic motor, has been unprofitable since 2002 and has turned a loss for 8 of the last 12 years. Sales have fallen dramatically from mid-1990s levels and the business has been severely weighed down by its sponsorship of fraternal activities, which have generally cost about $1 million per year to sustain. This has prompted an alarming reduction in the UNA s overall wealth, forcing the association to liquidate real estate assets to keep itself afloat. Reviving the insurance business would require a substantial and sustained boost in sales. But such a turnaround is unlikely the association s insurance products compete directly with the lower-priced, well-marketed offerings of large commercial insurance companies. This competitive disadvantage, faced by most other fraternal benefit societies, is a structural one about which there is very little management can do. In this report, I forecast how long the UNA can survive in its current form as well as how long it could live under several alternative organizational structures. I estimate that, if nothing changes (the insurance business continues to be the sponsor and administrator of fraternal activities), the insurance business only has enough capital to survive for another five to thirteen years and that the fraternal activities can be sustained until 2022 at the longest. Further, if the UNA is unable to sell property it owns in Jersey City, New Jersey by 2010, the insurance business and the fraternal activities will both die the following year. My recommendation for the future course of the UNA is to sell the insurance portfolio and to restructure into a cultural endowment dedicated to promoting and preserving the fraternal activities. I hold this opinion for three reasons. Firstly, according to my survivability estimates, the fraternal activities would live longest if the association were structured as an endowment. Such a restructuring would bring no hardship to owners of UNA insurance their policies would merely be administered by a different (and probably a financially healthier) party at no additional cost. Secondly, with UNA management focused on the fraternal activities and no longer busy trying to turn around a structurally uncompetitive insurance business, the performance of the fraternal activities would likely improve substantially. Thirdly, many Ukrainian-Americans make financial contributions to the UNA for the sake of preserving the fraternal activities. An endowment would not only be the most efficient and productive vehicle for these funds it would also the only one that, with enough support, would make it possible for the fraternal activities to live forever.